Ultra-low power OTA based on bias recycling and subthreshold operation with phase margin enhancement. (February 2017) - Ragheb, A.N.; Kim, HyungWon
Abstract: An ultra-low power and wide bandwidth operational transconductance amplifier (OTA) is presented. The proposed OTA employs a folded cascode (FC) structure with an enhanced current recycling technique. It provides the advantages of rail-to-rail input and output swing, while presenting lower power consumption and higher DC gain than conventional FC. It substantially reduces the power consumption by operating all devices under subthreshold region. In addition, it improves the phase margin of the OTA via special property of all-subthreshold operation – substantially enhanced recycling effect of RFC OTA that ensures high gain and bandwidth. We implemented the proposed OTA in a 65 nm CMOS process technology. The post layout simulation results demonstrate a robust performance exhibiting a DC-gain of 50.7 dB, and a unity gain bandwidth of 2.1 KHz –27.3 MHz for a capacitive load of 0.5 pF–15 nF. It also provides high phase margin (PM) up to 90 . 5 ° with extremely low power consumption of 3.9 μ W under a low supply voltage of 0.5 V.